1997
DOI: 10.3354/meps157221
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and lipid carbon stable isotope composition of the hydrothermal vent shrimp Mirocaris fortunata:evidence for nutritional dependence on photosynthetically fixed carbon

Abstract: Mjrocaris fortunata were sampled from the Lucky Strike hydrothermal vent area (Eiffel Tower site) on the mid-Atlantic ridge during the French DlVA 2 cruise (June 1994). Small adults (17 to 22 mm total length), although morphologically identical, could be divided into 2 categones on the basis of pigmentat~on, llpid composition and I3C/l2c stable isotope ratios of fatty acids H~ghly pigmented small adults (8 6 to 9.2 pg carotenoid shrimp-') contamed higher levels of total lipid than similar-sized individuals con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…Only juveniles above 1.2 cm were collected at the aggregates' periphery and are orange (Komai and Segonzac, 2008). Wax esters, fatty acids and fatty alcohols found in the juveniles indicated that they might feed for extended periods in the euphotic zone, allowing dispersion (Pond et al, 1997). This was supported by genetic data that suggested high gene flow in R. exoculata populations (Teixeira et al, 2011).…”
Section: Introductionsupporting
confidence: 62%
“…Only juveniles above 1.2 cm were collected at the aggregates' periphery and are orange (Komai and Segonzac, 2008). Wax esters, fatty acids and fatty alcohols found in the juveniles indicated that they might feed for extended periods in the euphotic zone, allowing dispersion (Pond et al, 1997). This was supported by genetic data that suggested high gene flow in R. exoculata populations (Teixeira et al, 2011).…”
Section: Introductionsupporting
confidence: 62%
“…References: (1) Ackman et al (1968), (2) Gillian & Hogg (1984), (3) Findlay et al (1990), (4) Volkman et al (1980), (5) present study, (6) Kayama et al (1989), (7) Erwin (1973), (8) Sargent et al (1987), (9) Zhukova & Kharlamenko (1999), (10) Pond et al (1997), (11) Nichols et al (1986) Table 6. Fatty acids and fatty acid ratios that were used as markers for food sources in the Zostera marina ecosystem.…”
Section: Discussionmentioning
confidence: 80%
“…Palmitoleic acid (16:1ω7) has been employed widely as a specific biomarker for microbial activity, particularly chemoautotrophic production (MacAvoy et al 2002a,b) but it may also originate from diatoms (Lewis 1969, Pond et al 1998 or be biosynthesized from other compounds. The δ 13 C signature of 16:1ω7 from sulfur-oxidizing bacteria is typically in the range of -28 to -35 ‰, while 16:1ω7 sourced from phytoplankton is more 13 C enriched (Pond et al 1997). In the present study, we observed that 16:1ω7 from red rock lobster mussel tissue was relatively more depleted in 13 C in inner Doubtful Sound (δ 13 C -30.65 ± 1.40 ‰, mean ± SE) than at Te Awaatu Channel (δ 13 C -23.68 ± 0.57 ‰) and at Kuta Parera Reserve (δ 13 C -22.1 ‰).…”
Section: Discussionmentioning
confidence: 99%